A high-resolution Late Glacial to Holocene record of environmental change in the Mediterranean from Lake Ohrid (Macedonia/Albania) - Lacey, Jack H.; Francke, Alexander; Leng, Melanie J.; Vane, Christopher H.; Wagner, Bernd (International Journal of Earth Sciences, 2014)
Abstract Lake Ohrid (Macedonia/Albania) is the oldest extant lake in Europe and exhibits an outstanding degree of endemic biodiversity. Here, we provide new high-resolution stable isotope and geochemical data from a 10 m core (Co1262) through the Late Glacial to Holocene and discuss past climate and lake hydrology (TIC, δ 13 C calcite , δ 18 O calcite ) as well as the terrestrial and aquatic vegetation response to climate (TOC, TOC/N, δ 13 C organic , Rock Eval pyrolysis). The data identifies 3 main zones: (1) the Late Glacial–Holocene transition represented by low TIC and TOC contents, (2) the early to mid-Holocene characterised by high TOC and increasing TOC/N and (3) the Late Holocene–Present which shows a marked decrease in TIC and TOC. In general, an overall trend of increasing δ 18 O calcite from 9 ka to present suggests progressive aridification through the Holocene, consistent with previous records from Lake Ohrid and the wider Mediterranean region. Several proxies show commensurate excursions that imply the impact of short-term climate oscillations, such as the 8.2 ka event and the Little Ice Age. This is the best-dated and highest resolution archive of past Late Glacial and Holocene climate from Lake Ohrid and confirms the overriding influence of the North Atlantic in the north-eastern Mediterranean. The data presented set the context for the International Continental scientific Drilling Program Scientific Collaboration On Past Speciation Conditions in Lake Ohrid project cores recovered in spring–summer 2013, potentially dating back into the Lower Pleistocene, and will act as a recent calibration to reconstruct climate and hydrology over the entire lake history.